Optimization of Power train Architectures and Control Strategies for Hybrid and Plug-in Hybrid Electric Vehicles - saurabh bagde, (IJRDO - Journal of Business Management, 2025)
Electric and hybrid electric vehicles (EV/HEV) are promising solutions for fossil fuel conservation and pollution reduction for a safe environment and sustainable transportation. The design of these energy-efficient power trains requires optimization of components, systems, and controls. Control sentail battery management, fuel consumption, driver performance demand emissions, and management strategy. The hardware optimization entails power train architecture, transmission type, power electronic converters, and energy storage systems. In this overview, all these factors are addressed and reviewed. A major challenge sand future technology for EV/HEV area is discussed. Published suggestions and recommendations are surveyed and evaluated in this review. The outcomes of detailed studies are presented in tabular form to compare the strengths and weaknesses of various methods. Furthermore, issues in the current research are discussed, and suggestions toward further advancement of the technology are offered. This article analyzes current research and suggests challenges and scope of future research in EV/HEV and can serve as a reference for those working in this field.